Rancang Bangun Sistem Informasi Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) dengan Metode Extreme Programming - Maria Ulfa Siregar; Hamid Musafa (UIN Sunan Kalijaga Yogyakarta, 2019)
Pamsimas or Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat, is a government program for rural communities that greatly helps the village government to provide water and sanitation needs for society. Therefore the management of Pamsimas becomes very necessary and important. But unfortunately the management of Pamsimas at the village level still uses manual methods. It really requires a lot of time and energy, given the large amount of data that must be managed in Pamsimas. This research has the purpose of creating a digital system that is able to makes management process of Pamsimas more effective and efﬁcient of time, effort and costs, with web base PHP programming language and MySQL database. The development method used in this study is extreme programming method. This method was chosen because it has good feedback or communication between the developer and client. Furthermore this methods whose stages are simple and also more ﬂexible to the changes that occur. The results of this research are a web-based digital information system that could make the process of managing data in Pamsimas more effective and efﬁcient, because this system is able to make reports and calculate bills automatically. So that the previous time spent by many managers becomes less, and because of that the energy spent is more effective.Keywords : Web Application, Information System, PAM System, PAM System Information, Laravel, Extreme Programming.